Nepalese Municipal Governance: A comparative case study of Kathmandu and Lalitpur metropolitan cities - Gyawali, Rajeshwor (Research Nepal Journal of Development Studies, 2018)
Kathmandu and Lalitpur are two metropolitan cities of the Capital of federal Republic Nepal. Both cities have many identical similarities in culture, language, taste, and preferences. However, there are substantial differences in governing facilities. So, to compare the Information and Communication Technologies (ICT) infrastructure, human resource capacity, opportunities and threats to adapt governance in Kathmandu and Lalitpur. Methodologically, in depth interview with IT officers of both metro cities and library method have been conducted. The information has been verified in the legislative declaration (Council Report). ICT Infrastructure and ICT based human resource capacity are better in Kathmandu whereas ICT Adaptation opportunities and threats both are higher in Lalitpur. In comparison, Kathmandu is more advanced. Both metro cities need to work a lot to provide smart facilities to people in global context. Research Nepal Journal of Development Studies Vol.1(1) 2018 66-72